2022
DOI: 10.3390/clinpract12050071
|View full text |Cite
|
Sign up to set email alerts
|

Severe Stenosis of Mitral Bioprosthetic Valve Thrombosis in a Patient with HCV-Related Cirrhosis and Duodenal Variceal Bleeding: The Deadly Triad

Abstract: Bioprosthetic valve thrombosis (BPVT) is considered a relatively rare but life-threatening clinical entity. Thus, there is the need of high clinical suspicion in order to make a timely diagnosis and related appropriate therapeutic interventions. In this regard, the management of BPVT is high risk, whatever the option taken (surgery and/or systemic fibrinolysis). The presence of severe comorbidities—as decompensated cirrhosis—further complicates the clinical decision-making process, calling for a patient-tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The presence of severe comorbidities—as decompensated cirrhosis—further complicates the clinical decision-making process, calling for a patient-tailored integrated multidisciplinary approach. Cocchia et al [ 21 ] reported here a challenging case of a 45-year-old patient with mitral bioprosthetic valve thrombosis and hepatitis C virus-related cirrhosis complicated by active duodenal variceal bleeding.…”
mentioning
confidence: 99%
“…The presence of severe comorbidities—as decompensated cirrhosis—further complicates the clinical decision-making process, calling for a patient-tailored integrated multidisciplinary approach. Cocchia et al [ 21 ] reported here a challenging case of a 45-year-old patient with mitral bioprosthetic valve thrombosis and hepatitis C virus-related cirrhosis complicated by active duodenal variceal bleeding.…”
mentioning
confidence: 99%